Implementation Of Green Marketing And Sustainability Accounting In Strengthening The Competitiveness Of Sustainability-Oriented Msmes - Yaskun, Mohammad; Mahmudah, Henny; Syafik, Muhammad; Arif, Rochman; Purnomo, Aji (Proceeding of International Management Conference and Progressive Papers, 2025)
A community service activity conducted in Lateg Village, Lamongan Regency, aimed to increase the competitiveness of MSMEs through the application of green marketing and sustainability accounting concepts. This program successfully raised awareness and skills of business actors in integrating sustainability values ​​into daily business practices, such as the use of environmentally friendly packaging, waste management, and simple recording of social and environmental costs. The results of the activity showed increased understanding, collaboration among business actors, and increased product sales after the implementation of green marketing strategies. However, there were several limitations, such as limited mentoring time, a small number of participants, and the lack of quantitative economic impact. In the future, similar activities need to be expanded to involve more MSMEs, support from financial institutions and local governments, and the involvement of the village’s younger generation as agents of digitalization and promotion of green products. With strengthened mentoring and cross-sector collaboration, Lateg Village has the potential to become a model of a sustainable village based on a green economy that is adaptive, independent, and competitive, while also supporting the achievement of the Sustainable Development Goals.